Una visión integral del ingeniero electrónico de la facultad de ingeniería - Betancourt Uscátegui, Álvaro (Ingeniería, 2000)
In the field of the engineering education and particularly of the engineering that prepares with integral vision, this paper intends a modification to the academic program of electronic engineering of our university.